Thermal micropolar and couple stresses effects on peristaltic flow of biviscosity nanofluid through a porous medium - Aya M. Ismael; Nabil T. Eldabe; Mohamed Y. Abou zeid; Sami M. El Shabouri (Scientific Reports, 2022)
Abstract The main aim of the current study is to analyze couple stresses effects on MHD peristaltic transport of a micropolar non-Newtonian nanofluid. The fluid flows through a porous media between two horizontal co-axial tubes. The effects of radiation, chemical reaction, viscous and ohmic dissipation are considered. The inner tube is solid and uniform, while the outer tube has a sinusoidal wave traveling down its wall. The governing equations have been simplified using low-Reynolds number and long wave-length approximations, thus a semi-analytical solutions have been obtained using the homotopy perturbation method. Numerical results for the behaviors of the axial velocity, microrotation velocity, temperature and nanoparticles concentration with the physical parameters are depicted graphically through a set of graphs. Furthermore, the values of the skin friction coefficient, Nusselt and nano Sherwood numbers are computed and presented graphically through some draws. Moreover, the trapping phenomenon is discussed throughout a set of figures. The present study is very important in many medical applications, as the gastric juice motion in the small intestine when an endoscope is inserted through it. Further, gold nanoparticles are utilized in the remedy of cancer tumor.